2018
DOI: 10.3390/ma11061004
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Degradation of Malachite Green in Seawater by the Hybrid of Zinc-Oxide Nanorods Grown on Three-Dimensional (3D) Reduced Graphene Oxide(RGO)/Ni Foam

Abstract: A hybrid of ZnO nanorods grown onto three-dimensional (3D) reduced graphene oxide (RGO)@Ni foam (ZnO/RGO@NF) is synthesized by a facile hydrothermal method. The as-prepared hybrid material is physically characterized by SEM, XRD, Raman, and X-ray photoelectron spectroscopy (XPS). When the as-prepared 3D hybrid is investigated as a photocatalyst, it demonstrates significant high photocatalytic activity for the degradation of methylene blue (MB), rhodamine (RhB), and mixed MB/RhB as organic dye pollutants. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Meena and coworkers have reported a similar study using EDTA, oleic acid and citric acid capped ZnO nanoparticles . High photocatalytic performance for the elimination of MG in seawater was reported using ZnO/RGO@NF under UV illumination . The reaction was carried out undersimilar experimental conditions using different amounts of catalyst for 60 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meena and coworkers have reported a similar study using EDTA, oleic acid and citric acid capped ZnO nanoparticles . High photocatalytic performance for the elimination of MG in seawater was reported using ZnO/RGO@NF under UV illumination . The reaction was carried out undersimilar experimental conditions using different amounts of catalyst for 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…[15] High photocatalytic performance for the elimination of MG in seawater was reported using ZnO/ RGO@NF under UV illumination. [21] The reaction was carried out undersimilar experimental conditions using different amounts of catalyst for 60 min. From Figure 7B, it is clear that the optimum amount of catalyst that shows maximum degradation efficacy is 0.1 g. Ajay et al have reported a similar degradation study of MG using PEG capped zinc oxide nanoparticles under visible light illumination.…”
Section: Optimization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the various nanomaterials mentioned earlier, hybridization of these nanomaterials with other materials was utilized to exploit their exceptional functionality and to develop outstanding hybrid nanomaterials for application in various scientific fields [78][79][80]. The developed hybrid nanomaterials showed excellent electrochemical, plasmonic, and photoluminescent properties not present before the hybridization [81,82].…”
Section: Hybrid Nanomaterial-based Biosensorsmentioning
confidence: 99%
“…It is of great significance to promote the practical application of nanomaterials to assemble macroscopic structures with nanomaterials while maintaining their original properties and interaction strength. Recently, we find that a new type of three-dimensional (3D) graphene foam can not only avoid the stack of graphene nanosheets and effectively maintain its large specific surface area but also can minimize the reflection of incident light and improve the efficiency of light utilization [25,26]. Meanwhile, it can be easily separated and recovered.…”
Section: Introductionmentioning
confidence: 99%